Benfotiamine, a Lipid-Soluble Analog of Vitamin B1, Improves the Mitochondrial Biogenesis and Function in Blunt Snout Bream (Megalobrama amblycephala) Fed High-Carbohydrate Diets by Promoting the AMPK/PGC-1β/NRF-1 Axis - Xu, Chao; Liu, Wen-Bin; Zhang, Ding-Dong; Shi, Hua-Juan; Zhang, Li; Li, Xiang-Fei (Frontiers in Physiology, 2018)
This study evaluated the effects of benfotiamine on the growth performance and mitochondrial biogenesis and function of Megalobrama amblycephala fed high-carbohydrate diets. Fish (45.25 ± 0.34 g) were randomly fed six diets: the control diet (30% carbohydrate, C), the high-carbohydrate diet (43% carbohydrate, HC) and the HC diet supplemented with different benfotiamine levels (0.7125 (HCB1), 1.425 (HCB2), 2.85 (HCB3) and 5.7 (HCB4) mg/kg) for 12 weeks. High-carbohydrate levels remarkably decreased weight gain rate, specific growth rate, relative feed intake, feed conversion ratio, p-AMPKα/t-AMPKα ratio, peroxisome proliferator activated receptor-γ coactivator-1β (PGC-1β) and nuclear respiratory factor-1 (NRF-1) protein expression, complexes I, III and IV activities and hepatic transcriptions of cytochrome B (CYT-B) and cytochrome c oxidase-2 (COX-2), whereas the opposite was true for plasma glucose, glycated serum protein, advanced glycation end products and insulin levels, tissue glycogen and lipid contents, hepatic adenosine triphosphate (ATP) and adenosine monophosphate (AMP) contents and ATP/AMP ratio, complexes V activities and the expressions of AMP-activated protein kinase α-2 (AMPKα-2), PGC-1β, NRF-1, mitochondrial transcription factor A (TFAM), mitofusin-1 (Mfn-1), optic atrophy-1 (Opa-1), dynamin-related protein-1 (Drp-1), fission-1 (Fis-1), mitochondrial fission factor (Mff) and ATP synthase-6 (ATP-6). As for benfotiamine supplementation, HCB2 diet remarkably increased weight gain rate, specific growth rate, tissue glycogen and lipid contents, AMP contents, p-AMPKα/t-AMPKα ratio, PGC-1β and NRF-1 levels, complexes I, III, IV and V activities and hepatic transcriptions of AMPKα-2, PGC-1β, NRF-1, TFAM, Mfn-1, Opa-1, CYT-B, COX-2 and ATP-6, while the opposite was true for the remaining indicators. Overall, 1.425 mg/kg benfotiamine improved the growth performance and mitochondrial biogenesis and function of fish fed high-carbohydrate diets through the activation of AMPK/PGC-1β/NRF-1 axis, the up-regulation of mitochondrial complexes activities and transcriptions as well as the enhancement of mitochondrial fusion coupled with the depression of mitochondrial fission.